2006
DOI: 10.1093/ps/85.10.1764
|View full text |Cite
|
Sign up to set email alerts
|

Production of Chick Germline Chimeras from Fluorescence-Activated Cell-Sorted Gonocytes

Abstract: Modification of the chicken germline has been difficult, because it has been challenging to fractionate sufficient numbers of primordial germ cells for manipulation and implantation into developing embryos. A technique to enrich cell suspensions for primordial germ cells, using fluorescence-activated cell sorting (FACS), has recently been developed. The objective of the current study was to demonstrate that the FACS-enriched early embryonic gonocytes could fully participate in development of the germline. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 27 publications
1
29
0
1
Order By: Relevance
“…Germ cells freshly isolated from the gonad have been shown previously to contribute to the germline after injection into recipient embryos [23,24]. This study shows that these gonocytes can retain their potential in culture and contribute to the germline.…”
Section: Germline Transmissionsupporting
confidence: 51%
“…Germ cells freshly isolated from the gonad have been shown previously to contribute to the germline after injection into recipient embryos [23,24]. This study shows that these gonocytes can retain their potential in culture and contribute to the germline.…”
Section: Germline Transmissionsupporting
confidence: 51%
“…3). This level of PGC purity is equal to those achieved with the FACS [4] and Nycodenz [8] methods. The red blood cells disappeared and the PGCs appeared when isolated whole blood was cultured for 1-2 weeks [19].…”
Section: Discussionmentioning
confidence: 61%
“…ACK lysis buffer consisted of 150 mM NH 4 Cl, 1 mM KHCO 3 , and 0.001 mM EDTA. The buffer was filter-sterilized through a 0.2-lm filter, and the prepared blood sample was added to 900 ll of ACK lysis buffer.…”
Section: Composition Of Ack Lysis Buffer and Cpgc Purificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Naito et al (2004) demonstrated that PGCs isolated from blood, and transferred to blastoderms in X stage, could enter in the bloodstream and migrate to the gonadal ridges of recipient embryos. Mozdziak et al (2006) used FACS to enrich PGC populations from gonocytes. Cell preparations obtained from male gonads from 10-14 embryos at stage 27 were incubated with a monoclonal antibody against SSEA-1, and fluorescently labeled cells were separated from non-reactive cells using FACS.…”
Section: Isolation Of Pgcs and Generation Of Pgc-derived Progenymentioning
confidence: 99%